(3JMaI GdQGZHjJ aj JMQjQ efgGL GdWGdHjfs - (3GHf GdEeGes
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdHQ GdLhGO CeG HYO bO CcKQ CUMGHfG ajg ef GdJUfja ef GdeHShWGJ hGdeNJUQGJ hCJbf eNJUQ GdefgGL ddTjN CHj RcQjG Gdfhhj heNJUQ GdeMQQ ddEeGe EeGe GdOjf GdQGaYj aQCjJ LejYgG aj eDda eY eQGYGI YHGQI GdefgGL MSH GdEecGf hJejjR eG ROJg ef GdJUMjM hZjQg HGdMeQI aj eMdg (B-- (3hSejJ cJGHj gPG JMaI GdQGZHjfs
(3BNQgG (B:s
(3dh hWFgG RhLgG Ydi Xf CfgG MQI aGdhdO MQ hYdjg bjeJg dSjOgG hChdGOgG bHd GdGSJjdGO ef RfG Gh RhL dG jYJbhf HehJ GdSjO hdg HjYe EdG EPG hdOhG aj edcg hYJb GdeSJhdOI hChdGOgG hdh aj GdeQV hef eOjhf ef QCS GdeGd CYJbfG Gddg GdfcGQ hMTQfG aj ReQI GdEHOGd hEfg GdeLjH GdcHjQ GdeJYGds
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc (B: (3GdMGL UGdM GdNjGW (B- (3GdMGL eUWai UObj GHf GdTgjO GdMGL eMehOGdCfWGcj hbag Ydi JcjI bWH GdYGQajfs
Keywords: (3Gdabg GdTGaYjs